(untitled) (Research, Society and Development, 2021)
Remote learning was the form of teaching adopted in Brazil to meet the need for social distancing, driven by the COVID-19 pandemic. In this context, the monitoring program gains relevance when understood as a pedagogical support tool. The objective of this paper is to report the experiences of academic monitoring, in the remote modality, experienced in the discipline of "Health Education", during the COVID-19 pandemic, in a technical nursing course, from the perspective of the academic monitor. This is a descriptive study, of the experience report type, based on the report of the experiences of monitoring in the Health Education discipline, in the context of remote teaching, of a Nursing Technician course in a federal educational institution in northeastern Brazil. Some communication tools were used to carry out the activities, such as Google Classroom, Google Meet, Whatsapp and Canva. The activities carried out by the monitors included: bibliographic surveys related to “Health Education”; production of teaching materials: Video and Primer. The monitors carried out their activities to assist students through scheduling, meetings on Google Meet and Whatsapp groups. From this work, it was found that, given the educational panorama, affected by the COVID-19 pandemic, remote monitoring has become an essential object to help teachers in the teaching-learning process, constituting a field of knowledge for all those involved in the process, teachers, monitors and assisted students, in addition to closer interpersonal relationships, even in physical distance.